INFLUENCE OF COOPERATIVE LEARNING MODEL TYPE TGT (TEAM GAME TOURNAMENT) TO LEARNING OUTCOMES OF STUDENTS IN WORKING PRINCIPLE OF THE BATTERY AND BATTERY CONSTRUCTION FOR CLASS X OF SMK TKR KARSA MULYA PALANGKARAYA ACADEMIC YEAR 2015/2016 - Okta Simson; Wiyogo (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2016)
The Difficulties faced by students in understanding the working principles of battery material and battery construction with conventional learning models can be seen from the results of student learning which is still at under KKM 68 while for school standard is 70. This study aims to determine the effect of cooperative learning model TGT (Team Game Tournament) to the study of students in the material working principle batteries and battery construction in class X SMK TKR Karsa Mulya Palangkaraya Academic Year 2015/2016. This type of research is True Experiment Design type using Posttest Control Design. The population of this research is class X TKR, TSM A, and TSM B using the sample is random sampling. Its results have been obtained from class X Mechanical Light Vehicle as a class experiment with a number of 40 students and class X of Motorcycle Engineering A as grade control with number 36 students. Data is collected using a test that is posttest. The collected data was analyzed statistically using the values and the difference in the two values of posttest. Based on the results of data analysis posttest value, there are average class experiment (81.30) and the control class (71.34). Accordance of the calculation of the difference between two average - average class experimental and control classes with significant level of 5% was obtained price table = 2.001 and calculations are t = 4.40, then the result is: t = 4.40> table = 2.001. These mean that H0 and H1 accepted. Ultimately it can be sum med up that the results for students taught by cooperative learning model TGT (Team Game Tournament) showed the well performance than students who using the conventional learning models (cermah) on the material working principle batteries and battery construction.